2022
DOI: 10.30965/22142290-12340019
|View full text |Cite
|
Sign up to set email alerts
|

Introduction

Abstract: Gender-based violence, (geo)politics, and Islam continue to dominate the production of knowledge about Central Asia. While using a gender lens, this Special Issue offers a different perspective on the region. The authors link historical analyses of imperial and Soviet gendered modernities to contemporary Central Asians’ daily lives and local nationalisms to shed light on often overlooked areas in the literature, such as a systematic screening out of historical and contemporary gender diversity, sex work, virgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…As pointed out by Craig Calhoun (2007), 'tradition' is not only a fixed past, rather it is a political project that is continuously reinvented and reproduced. In Central Asia, traditional values discourses generally represent patriarchal and heterosexual normative behaviour as well as a binary view of gender (for example, Peshkova & Thibault, 2022;Kudaibergenova, 2019). In her study of popular Instagram accounts in Kazakhstan and Russia, Diana Kudaibergenova highlights the role of retraditionalisation in defining and regulating sexual identities and bodily expressions.…”
Section: Queer Children and Young People In Kazakhstanmentioning
confidence: 99%
“…As pointed out by Craig Calhoun (2007), 'tradition' is not only a fixed past, rather it is a political project that is continuously reinvented and reproduced. In Central Asia, traditional values discourses generally represent patriarchal and heterosexual normative behaviour as well as a binary view of gender (for example, Peshkova & Thibault, 2022;Kudaibergenova, 2019). In her study of popular Instagram accounts in Kazakhstan and Russia, Diana Kudaibergenova highlights the role of retraditionalisation in defining and regulating sexual identities and bodily expressions.…”
Section: Queer Children and Young People In Kazakhstanmentioning
confidence: 99%
“…The scholarship on gendered nationalism in Central Asia discusses the narratives both during the Soviet times and during the independence of the states in the region (Cleuziou & Direnberger, 2016;Kandiyoti, 2007;Peshkova & Thibault, 2022). A recent study based on the discourses of feminist activists revealed several contesting discourses that touched upon "nationalism and decolonization" as well as "oppressive and emancipatory" Soviet legacy (Kravtsova, 2022, p. 83).…”
Section: Nation-building and Gender In Kazakhstanmentioning
confidence: 99%